Pengaruh Komitmen Dosen-Dosen Akuntansi Terhadap Perkembangan Profesi Akuntansi, Motivasi sebagai Variabel Intervening - Robertha Titik Dyah Ratna Ngesti Utami (Jurnal Akuntansi, 2010)
This Research id to determine (1) Significant effect of organizational commitment, professional commitment and development of Accounting Profession (2) The significant effect of organizational commitment,professional commitment and motivation (3) Significant effect between motivation and the Development of Accounting Profession (4)Indirect significant effect of organizational commitment and professional commitment to the development of Professional Accounting through motivation as an intervening variable. This research was conducted on Private Higher Education in Kopertis Region IV. With the unit of analysis are lecturers in accunting. Empirical research conducted on 215 respondents with a random sampling method and use path analysis method. Results showed that (1) the effect of organizational commitmend to the motivation is 4,172% (2) The effect of professional commitment to the motivation is 84,32% (3) The effect or organizational commitment to the development of the accounting profession by 34,03%, (4) The effect of professional commitment on the development or accounting profession is 14,32%, (5) The effect of motivation on the development of accounting profession is 5,23% (6) The effect of organizational commitment to the development of the accounting profession through the motivation is 5,08%. (7) The effect of professional commitment to the development of the accounting profession through the motivation is 67,60%. Keywords: Organizational Commitment, Motivation and Development of Accounting Profession